1984
DOI: 10.1128/aac.26.1.53
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms of action of aminoglycoside antibiotics in eucaryotic protein synthesis

Abstract: Tetrahymena thermophila is a eucaryotic organism that is highly susceptible to growth inhibition by aminoglycoside antibiotics. Concentrations of paromomycin, gentamicin G418, and hygromycin B at 22, 10, and 17 ,uM, respectively, inhibited growth by 50%. A combination of in vitro and in vivo methods was used to determine the mechanisms of action of these aminoglycoside antibiotics on protein synthesis in T. thermophila. Analysis of polysome profiles from paromomycin-and gentamicin G418-treated cells showed cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…These findings agree with our data; however, Aufsatz et al report that resistance is kanamycin specific and does not carry over to gentamicin or hygromycin. We did not see hygromycin resistance in any of our mar1 mutants, which was expected because hygromycin has effects against eukaryotic ribosomes and therefore acts in the cytoplasm of the plant cell (Eustice and Wilhelm, 1984). However, we do show that mar1 mutants are multiply resistant to several aminoglycosides, including gentamicin (Fig.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…These findings agree with our data; however, Aufsatz et al report that resistance is kanamycin specific and does not carry over to gentamicin or hygromycin. We did not see hygromycin resistance in any of our mar1 mutants, which was expected because hygromycin has effects against eukaryotic ribosomes and therefore acts in the cytoplasm of the plant cell (Eustice and Wilhelm, 1984). However, we do show that mar1 mutants are multiply resistant to several aminoglycosides, including gentamicin (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…S1 and S2). These compounds, while structurally similar to other aminoglycosides, are distinct in that they inhibit both prokaryotic and eukaryotic protein synthesis (Eustice and Wilhelm, 1984). No resistance was found to antibiotics of other classes, including spectinomycin (an aminocyclitol), tetracycline, chloramphenicol, and lincomycin (Fig.…”
Section: Isolation and Map-based Cloning Of The Multiplementioning
confidence: 99%
“…In spite of the literature that demonstrated aminoglycosides inhibited protein synthesis [17,18], the selective inhibition of viral cytopathology by only G418 suggested that the antiviral activity of this aminoglycoside is different from that commonly seen with inhibitors of viral translation and replication. To assess the effect of G418 on the translation of viral proteins, we used viral NS3 protein as a marker of BVDV translation at 24 h post-infection with an MOI of 10.…”
Section: Resultsmentioning
confidence: 82%
“…Moreover, G418 did not inhibit viral RNA synthesis, suggesting that it did not affect viral polymerase (NS5B) formation and activity. These data suggest that G418, although being an inhibitor of protein synthesis [17,18], could possibly inhibit virus-induced cytopathology without blocking translation or replication. In addition, because virus entry precedes translation, it is highly unlikely that G418 blocks viral mechanisms before translation and replication.…”
mentioning
confidence: 99%
“…5 GUS expression at two stage 5a GUS foci in callus on resting medium (after 6-days co-cultivation); 5b GUS expression in leaf tissues of green shoots developed on RSM medium compared with non-transformed control leaf tissue from seedling All these data were resulted from three replicates with 25 calli per replication; data are presented after arcsine transformations as avg. means ± standard error followed by the same letter are not significantly different from each other (LSD > 0.05) Wilhelm 1984). When the treatment 9 was used in the selection media against transformed rice calli for 8 weeks, it resulted in survival of only the transgenic calli.…”
Section: Plant Selection Markermentioning
confidence: 84%